The many colours of the TNG100 simulation - Gebek, Andrea; Trčka, Ana; Baes, Maarten; Martorano, Marco; Pillepich, Annalisa; Kapoor, Anand Utsav; Nersesian, Angelos; van der Wel, Arjen (Monthly notices of the Royal Astronomical Society, 2024)
We apply the 3D dust radiative transfer code skirt to the low-redshift (z ≤ 0.1) galaxy population in the TNG100 cosmological simulation, the fiducial run of the IllustrisTNG project. We compute global fluxes and spectral energy distributions (SEDs) from the far-ultraviolet to the submillimetre for $≈ 60\, 000$ galaxies, with the same post-processing methodology that was previously applied to the TNG50 simulation. We verify that TNG100 reproduces observational luminosity functions at low redshifts to excellent precision, unlike TNG50. Additionally, we test the realism of our TNG100 plus skirt fluxes by comparing various flux and colour relations to data from the GAMA survey. TNG100 broadly reproduces the observed distributions, but we predict ultraviolet colours that are too blue by $≈ 0.4\, mag$, possibly related to the extinction in the star-forming regions subgrid model not being selective enough. Furthermore, we find that the simulated galaxies exhibit mid-infrared fluxes elevated by up to $≈ 0.5\, mag$ that we attribute to overly effective stochastic heating of the diffuse dust. All synthetic broad-band fluxes and SEDs are made publicly available in three orientations and four apertures, and can readily be used to study TNG100 galaxies in a mock observational fashion.
Veröffentlicht: 3. Juni 2024
Gesehen am 26.11.2024